Diblock copolymers directing construction of hierarchically porous metal-organic frameworks for enhanced-performance supercapacitors. (29th January 2021) - You, Yuxiu; Li, Fanggang; Ai, Yan; Wei, Facai; Cui, Jing; Fu, Jianwei; Zheng, Maojun; Liu, Shaohua
Abstract: A rationally designed strategy is developed to synthesize hierarchically porous Fe-based metal-organic frameworks (P-Fe-MOF) via solution-based self-assembly of diblock copolymers. The well-chosen amphiphilic diblock copolymers (BCP) of polystyrene-block-poly(acrylic acid) (PS -b- PAA) exhibits outstanding tolerance capability of rigorous conditions (e.g. strong acidity or basicity, high temperature and pressure), steering the peripheral crystallization of Fe-based MOF by anchoring ferric ions with outer PAA block. Importantly, the introduction of BCP endows MOF materials with additional mesopores (∼40 nm) penetrating whole crystals, along with their inherent micropores and introduced macropores. The unique hierarchically porous architecture contributes to fast charge transport and electrolyte ion diffusion, and thus promotes their redox reaction kinetics processes. Accordingly, the resultant P-Fe-MOF material as a new electrode material for supercapacitors delivers the unprecedented highest specific capacitance up to 78.3 mAh g −1 at a current density of 1 A g −1, which is 9.8 times than that of Fe-based MOF/carbon nanotubes composite electrode reported previously. This study may inspire new design of porous metal coordination polymers and advanced electrode materials for energy storage and conversion field.